2017
DOI: 10.1038/tpj.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR, TS and XRCC1 genetic variants may affect survival in patients with myelodysplastic syndromes treated with supportive care or azacitidine

Abstract: We evaluated the impact of genomic polymorphisms in folate-metabolizing, DNA synthesis and DNA repair enzymes on the clinical outcome of 108 patients with myelodysplastic syndromes (MDS) receiving best supportive care (BSC) or azacitidine. A statistically significant association between methylenetetrahydrofolate reductase (MTHFR) 677T/T, thymidylate synthase (TS) 5′-untranslated region (UTR) 3RG, TS 3′-UTR − 6 bp/ − 6 bp, XRCC1 399G/G genotypes and short survival was found in patients receiving BSC by multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[16][17][18] However, a recent review concluded that there was no association or opposite effects in the majority of published data, and that these two polymorphisms are not suitable predictors of outcome in pediatric ALL. 5 However, the MTHFR 677TT homozygous genotype has been associated with shorter survival in patients with myelodysplastic syndromes 41 .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, a recent review concluded that there was no association or opposite effects in the majority of published data, and that these two polymorphisms are not suitable predictors of outcome in pediatric ALL. 5 However, the MTHFR 677TT homozygous genotype has been associated with shorter survival in patients with myelodysplastic syndromes 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TS may be involved in the etiopathogenesis of AML. MTHFR c.*177C>G (rs1801133), TS c.*450_*455del (rs11280056) and X-ray repair cross complementing 1 (XRCC1) (DNA repair protein) c.*310A>C (rs25487) mutated alleles have been associated with shorter survival in patients with myelodysplastic syndromes treated with azacitidine versus patients who only received supportive care [ 102 ]. This associated should also be evaluated in AML patients.…”
Section: Hypomethylating Agentsmentioning
confidence: 99%
“…Three single nucleotide polymorphisms (SNPs), XRCC1 rs25487 G/A, XRCC3 rs861539 C/T and ADPRT rs1136410 T/C were analyzed by PCR-RE assay, as previously reported [8]. Primer sequences, preparative PCR conditions and additional details for the RE analysis are reported in Supplementary Table 2.…”
mentioning
confidence: 99%
“…Primer sequences, preparative PCR conditions and additional details for the RE analysis are reported in Supplementary Table 2. Statistical analysis was conducted as previously reported [8]. For all the target polymorphisms, the distribution of genotypes was checked for Hardy-Weinberg equilibrium.…”
mentioning
confidence: 99%